DISTRIBUTION OF ELECTRONIC BOOKS IN SWEDEN - Macevičiūtė, Elena (Knygotyra, 2016)
The article presents the results of two surveys carried out in Sweden and related to the electronic books. One of them was conducted in 2012 and directed towards public libraries. The other one, conducted in 2014, involved physical bookshops and the attitudes of their staff regarding e-books. The result has shown that physical bookshops are not dealing in electronic book sales, but the majority of public libraries are providing access to e-books. The bookshops do not feel any threats coming from this new technology and do not invest in expensive and uncertain technology needed for selling them. Public libraries are trying to overcome and increase the borrowing of e-books through libraries and succeed in that, though the loans of e-books account for a small fraction of all loans in public libraries. Libraries engaging in this new type of services encounter many problems with provision, limitations, budgeting and managing of electronic books, however, they are not going to drop this activity in the nearest future and look for the solutions to all existing problems.
Keywords: ...